2014
DOI: 10.15446/rsap.v16n4.40653
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la lactancia materna y factores asociados en Puerto Carreño, Colombia

Abstract: RESUMENObjetivo Caracterizar el uso de la lactancia materna en Puerto Carreño e identificar los factores asociados a brindar leche materna al recién nacido, lactancia exclusiva y lactancia materna total. Métodos Estudio transversal descriptivo por medio de encuestas estructuradas e individuales no aleatorias a 609 madres. El análisis incluyó métodos univariados, bivariados, curvas de supervivencia y modelos de regresión de logística binaria y riesgos proporcionales de Cox. Resultados La duración de la lactanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
4
0
5
Order By: Relevance
“…According to the results of this study, the CF is a social practice that results from the mixture of medical and popular knowledge, however, the degree of influence that the latter has on mothers is higher, mainly because of the degree of closeness and the accompaniment that they have from their close circle, especially from their mothers, grandmothers, and female relatives 37 .…”
Section: Discussionmentioning
confidence: 83%
“…According to the results of this study, the CF is a social practice that results from the mixture of medical and popular knowledge, however, the degree of influence that the latter has on mothers is higher, mainly because of the degree of closeness and the accompaniment that they have from their close circle, especially from their mothers, grandmothers, and female relatives 37 .…”
Section: Discussionmentioning
confidence: 83%
“…After an elapsed time, higher than 24 months, caregivers may tend to report the desired duration rather than what was practiced (World Health Organization, 2013). Then if this were the case, the study would show a lower desired breastfeeding duration than the duration -six months for exclusive breastfeeding and 2 years for continued breastfeeding combined with solids-proposed by national governmental guidelines from Colombia and/or international organizations like WHO (Niño, 2014;World Health Organization, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Most of these studies concluded that breastfeeding duration was shorter than the recommended breastfeeding duration proposed by international organizations and the Colombian government (Benjumea et al, 2011;Cabrera et al, 2004;Gómez-Aristizábal et al, 2013). Conversely, Niño (2014) found higher EBF rates than the duration proposed by national and regional governmental intervention programs in Colombia.…”
Section: Breastfeeding Practices In Colombiamentioning
confidence: 98%
See 1 more Smart Citation
“…Las causas asociadas al destete temprano fueron: 27.2% la decisión materna, 24.1% percibían sensación de hambre infantil, 17.3% por factores estéticos y 13% por enfermedad del niño. La LME hasta los seis meses se asoció con experiencias previas de LM exitosa con un nivel de asociación de 5.4 veces más con respecto a aquellas que no tuvieron experiencias previas exitosas (OR: 5.4, IC 2.2-13.2), mayor en el caso del sexo femenino del hijo con un OR: 5.5, (IC 2.5-12.3), la menor escolaridad materna OR: 5.4, (IC 2.4-11.7) y la atención en el sistema público de salud OR: 2.1, (IC 1.0-4.5) (Niño, 2014).…”
Section: Introductionunclassified